Self‐control or social control? Peer effects on temptation consumption. - Chuang, Yating (Southern Economic Journal, 2024)
This paper examines peer effects on self‐control problems. I construct a theoretical model to describe how peer networks influence consumption behaviors through social norms. Using monthly survey data conducted in 16 Thai villages from 1999 through 2004, I find that peer's temptation consumption significantly impacts individuals' temptation consumption such as alcohol, tobacco, and gambling. A one baht (around $0.025 U.S. dollars) increase in peer's temptation consumption leads to a 1.5 times increase in one's own temptation consumption. With detailed household‐level social network information defined by actual transactions, this paper identifies peer effects using a friend of a friend (excluded network) as the instrument. The panel nature of this instrument overcomes various common identification challenges, such as reflection, correlated effects, and common unobservable shocks, in the literature. My findings suggest that these peer effects are driven primarily by social norms, rather than risk sharing.